Maximising the potential of dynamic IT capabilities in merged firms : a due diligence consideration for Merger and Acquisition (M&A) operational systems integration alignment in South Africa - Pelser, Theuns (University of Pretoria, 2025)
Mini Dissertation (MBA)--University of Pretoria, 2024.